Model Problem Based Learning (PBL) Dengan Media Tiktok Terhadap Keterampilan Berpikir Kritis Siswa Pada Mata Pelajaran Biologi Materi Perubahan Lingkungan - Adi Wiguna Pratama Jayadinata; Ina Setiawati; Agus Prianto (Mahesa Research Center, 2023)
The primary goal of the curriculum is to help students develop into individuals with high reasoning power and critical thinking abilities that are up to date demands during the learning process. However, students' critical thinking abilities are actually below average. The study's objective was to investigate how students' critical thinking abilities were affected by the PBL model and TikTok media. Pretest and posttest group designs were used in the quasi-experimental research design. For the 2022/23 school year, all class X students at SMAN 1 Garawangi serve as the research population. Using the purposive sampling method, samples were taken. Through questionnaires and essay tests, gather research data. then processed using methods of quantitative data analysis. The most noteworthy sign of decisive reasoning abilities is deciding an activity because of the utilization of TikTok media in the PBL model. so that students can figure out how to solve the poorly structured problems and better understand them. The hypothesis test with the t test yielded results of 3.98 1.99, indicating that the PBL model and TikTok media have a significant impact on students' critical thinking abilities.